Frontispiece: How Science Can Contribute to the Remedial Conservation of Cultural Heritage. Issue 42 (26th July 2021) - Baglioni, Piero; Chelazzi, David
Abstract : The preservation of Cultural Heritage calls for tailored solutions to prevent the loss of this inheritance. Answering this call, materials and colloids sciences have been providing valid solutions. We review here the milestones and latest innovations in the development of advanced and nanomaterials for the remedial conservation of artifacts, illustrating successful case studies on classic and modern art, from archaeological sites and Renaissance frescos to Pablo Picasso and others. For more information, see the Minireview by D. Chelazzi and P. Baglioni on page 10798 ff.